Implikasi Metode Menghafal Al-Qur’an dalam Meningkatkan Kualitas Hafalan (Studi Komparatif di Pesantren Putri Al-Mardliyah Jombang dan Maahad Tahfiz Darul Falah Selangor) - Afinka Salsabila Irna Faizah; Farhan Masrury (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
Qur'anic memorization methods are a crucial element in tahfiz education as they carry significant implications for the quality of memorization proficiency. This study analyzes the implementation of Quranic memorization methods in improving memorization quality at Islamic Boarding School Al-Mardliyah Jombang (Indonesia) and Maahad Tahfidz Darul Falah Selangor (Malaysia). Employing a descriptive-comparative approach, the research explores methodological differences in tahfidz across countries, identifies supporting and inhibiting factors, and measures effectiveness within different socio-cultural contexts. Results indicate that Islamic Boarding School Al-Mardliyah implements a fixed 1:4 ratio (ziyadah and muraja’ah) with multi-layered evaluation structures, while Maahad Darul Falah employs a flexible approach with individualized ziyadah (0.5-5 pages) and stratified muraja'ah systems. Both methods effectively create conducive tahfidz environments with distinct advantages; Al-Mardliyah excels in discipline, order, and spiritual consistency through structured emotional guidance, whereas Darul Falah offers an inclusive-adaptive approach with strong institutional support and learning personalization. The research recommends integrating traditional pesantren disciplinary structures with modern pedagogical flexibility as an ideal model for developing quality-oriented and sustainable tahfidz programs. Keywords: Quranic Memorization, Tahfidz Methods, Ziyadah, Muraja'ah Islamic Boarding School Education